Peran Serikat Pekerja/Buruh dalam Penyelesaian Perselisihan Pemutusan Hubungan Kerja Secara Sepihak yang Dilakukan oleh Perusahaan terhadap Pekerja/Buruh - Ismi Pratiwi Podungge; David Patiolo; Vrisca Silvya; Isma Hanifa (CV Rewang Rencang, 2021)
This study aims to determine the role of trade unions in settling disputes over unilateral termination of employment by companies against employees. Termination of Employment Relations has a separate arrangement contained in Chapter XII Law No. 13 of 2003 concerning Employment. However, in practice in the field, this law still has several weaknesses, wherein the regulations there are loopholes that can make companies deviate from the content/meaning of the rules regarding Termination of Employment. In the era of the digitization of company equipment, employers terminated their employment on the pretext of company efficiency, which resulted in the removal of many employees' rights with the modernization of equipment. This has a big impact in the long run and further increases the unemployment rate in society. In addition to digitization, companies often use the pretext that termination of employment for company efficiency is permissible as long as it is in accordance with the provisions of laws and regulations. The type of research used by the author is a type of normative juridical research that focuses on the use of library data or secondary data in the form of primary, secondary, and tertiary legal materials. The data analysis used by the writer used the descriptive qualitative method, which is a description in the form of regular, coherent, logical, and effective sentences. Based on the results of this study, it can be seen that a trade union is very much needed in dealing with problems that exist in a company, one of which is the problem of termination of employment which is usually carried out unilaterally by the company and is detrimental to the employees himself. In this paper, the author also intends to compare the arrangement of the role of Trade Unions in termination of employment in Law No. 13 of 2003 Concerning Employment with Law No. 11 of 2020 concerning Job Excogitation.